Component Contracts in Service-Oriented Architectures. - Curbera, Francisco (Computer (00189162), 2007)
The article discusses service contracts in service-oriented architectures (SOAs). SOAs depend on software components developed by independent third parties, and the full potential of SOAs will not be achieved unless these components are governed by contracts more focused on quality of service (QOS). Fundamental QOS concerns are security, reliability, and the capacity to recover from errors. Packaged sets of components and wires are called composites. QOS properties for a composite can be specified in either a bottom-up or top-down manner.